Faktor yang Berhubungan dengan Kepatuhan Penderita Hipertensi dalam Menjalani Pengobatan di Wilayah Kerja Puskesmas Alak Kota Kupang - Anastasia De Yuni Kaha; Petrus Romeo; Marni Marni (Yayasan Literasi Sains Indonesia, 2026)
Hypertension is a non-communicable disease known as the “silent killer” because it often appears without symptoms, causing many individuals to remain unaware of their high blood pressure. The main factors contributing to hypertension are environmental factors, including family factors, community factors, and other related factors, namely the duration of hypertension, knowledge, family support, the role of health workers, and motivation to seek treatment. Data on hypertension cases in Kupang City were high in the period January - December 2023 recorded as many as 19,363 people suffering from hypertension, making hypertension one of the diseases with a fairly high number of cases in Kupang City. Data from the Community Health Center (Puskesmas) shows that Alak Community Health Center had the highest number of hypertension cases in Kupang City, namely 4,742 people throughout 2023. The purpose of this study was to analyze factors related to hypertension patient compliance with medication adherence in the Alak Community Health Center working area, Kupang City. This study involved 58 patients selected through accidental sampling. Data were analyzed using the chi-square test. The study results showed a relationship between compliance and patient knowledge (p = 0.011), family support (p = 0.013), and motivation to seek treatment (p = 0.002). Patients should undergo examinations as directed by healthcare professionals and adopt a healthy lifestyle to prevent more serious complications.